Sustainable viticulture in Bairrada appellation: vineyard and harvest year effects on grapes oenological potential - Petronilho, Sílvia Lancha (2015)
The sustainable viticulture of a region passes, among other aspects, for maximizing the varieties potential minimizing subsequent interventions during winemaking, which should contribute to the production of quality wines maintaining their typicity and rationalizing costs. The detailed knowledge of each Appellation specificities, namely vineyard parcel (soil type and topographical peculiarities) and harvest climatic conditions is crucial for sustainability in this sector. Thus, in line with this current trend, the starting point for the development of this PhD thesis was to evaluate the oenological potential of different varieties cultivated throughout Bairrada Appellation (Portugal). During maturation several changes in grape varieties occur, namely berries become sweeter, less acidic, and they develop flavour, aroma and colour properties. The development of these characteristics is essential to define grapes oenological potential, i.e. to estimate the possibility of their usage to produce specific wines. A three years sampling plan was designed to evaluate the effect of harvest year and parcel characteristics on V. vinifera cv. Arinto, Bical, Sauvignon Blanc, Baga, Castelão, Touriga Nacional, and Sousão grapes composition. For each variety, 3 parcels with different characteristics were selected. Several physicochemical parameters were evaluated, during maturation: berry weight, pH, titratable acidity, sugar and phenolic contents, antiradical activity, and volatile composition (free fraction). Special attention was devoted to grapes at technologic maturity, since, besides these parameters, glycosidically-linked fraction was also considered. By using the results obtained at technologic maturity, a comprehensive approach was applied to identify the significance of harvest and parcel characteristics effects on each variety composition. Considering all the parameters under study, it may be highlighted some significant differences. According to the obtained results determined during maturation, it was possible to conclude that Arinto, Bical and Sauvignon Blanc grapes from parcels with clay-sandy and clay-calcareous soils have higher phenolic content and antiradical activity. Otherwise, Sauvignon Blanc presented similar volatile composition for grapes cultivated in the 3 parcels, while Arinto and Bical exhibited higher volatile content in grapes from claysandy and clay-calcareous soils. For Baga, Castelão and Touriga Nacional red varieties, grapes with higher phenolic content, antiradical activity, and volatile content were obtained from clayey and clay-calcareous soils. Furthermore, for Touriga Nacional, parcels altitude seems also to modulate grapes composition. Beyond parcel effect, harvest year conditions also influence grapes composition: 2011 harvest was related with lower phenolic and volatile contents, as well as lower antiradical activity.For grapes collected at technologic maturity, analysis of variance-simultaneous component analysis (ASCA) was applied combining all the parameters under study, in order to assess the influence of harvest and parcel characteristics on each variety oenological potential. The results obtained using this comprehensive approach is closely related with those observed during maturation and revealed that harvest was the main factor that influenced grapes composition (53% to 68% of the total data set variance) followed by parcel characteristics, explaining ca. 15-19% of the total data set variance. The oenological potential of each variety may be different from one parcel to another, i.e., clay-sandy and clay-calcareous related-environments seem to favour Arinto and Bical white grapes composition, but for the red varieties, grapes composition was favoured by clayey and clay-calcareous soils. Besides, also higher altitude seems to favour Touriga Nacional grapes composition. Sauvignon Blanc seems to be a variety well adapted to the different parcel characteristics. In order to go forward in the valuation of these varieties, the aroma properties of 6 monovarietal wines were studied based on an aroma network-approach, linking molecular data related to volatile composition and aroma data about the key odor active molecules. This approach allowed to identify different wine aroma properties and to infer about the consumer’s sensory perception. It was found that aroma properties differ from one wine variety to another: while Arinto and Sauvignon Blanc wine exhibited higher tree fruity, sweety and flowery aromas, related essentially with ester compounds and C13 norisoprenoids, the opposite was obtained for Bical wine, corroborating the aroma sensory perceptions of the trained panel. Sauvignon Blanc also exhibited higher toasted aromas (related with thiols, mainly with 2-methyl-3-furanthiol). Touriga Nacional red wine exhibited higher tree, tropical, and berry fruits notes (sensory described as sweet fruits), toasted and flowery aromas, while these are similar for the other red wines under study. Besides Portuguese Bairrada wines, this aroma network approach is a tool that can be used to explain the aroma properties of wines worldwide. The grape and wine data generated under the present PhD thesis, in the context of Bairrada Appellation, shows the unique character of each variety, and may be used by growers and wine producers as a support for decisionmaking based on objective criteria, increasing the sustainability in this sector. For instance, it is possible to take advantage of the natural resources and produce products with different characteristics obtained from the same variety, minimizing costs during the winemaking process.